2022
DOI: 10.3390/jcm11061707
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Medication in Older Adults with Type 2 Diabetes Living in Lubuskie Voivodeship in Poland: Association with Frailty Syndrome

Abstract: Purpose: Diabetic patients aged 65 years or older are more likely to be frail than non-diabetic older adults. Adherence to therapeutic recommendations in the elderly suffering from diabetes and co-existent frailty syndrome may prevent complications such as micro- or macroangiopathy, as well as significantly affect prevention and reversibility of frailty. The study aimed at assessing the impact of frailty syndrome (FS) on the level of adherence to medication in elderly patients with type 2 diabetes (DM2). Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
1
7
0
Order By: Relevance
“…Available evidence had also revealed that age and sex had a significant relationship to anti-diabetic medication non-adherence and this also supports the outcome of this current study [36]. In addition, it is reported by a cross-sectional survey conducted in Poland that, adults aged 65 years and above do not comply with their medication and therefore suffer complications and as such do not relate well [37].…”
Section: Discussionsupporting
confidence: 87%
“…Available evidence had also revealed that age and sex had a significant relationship to anti-diabetic medication non-adherence and this also supports the outcome of this current study [36]. In addition, it is reported by a cross-sectional survey conducted in Poland that, adults aged 65 years and above do not comply with their medication and therefore suffer complications and as such do not relate well [37].…”
Section: Discussionsupporting
confidence: 87%
“…It is worth noting that elderly people with chronic diseases usually take several different types of medications, e.g in our study about 59% of the subjects had additional chronic diseases in addition to hypertension (multimorbidity phenomenon), and the average number of daily medications taken by a patient was 3.55 ±2.78. Correlation analysis did not show a significant relationship between the number of medications taken by patients and the level of adherence (p = 0.062), although other studies show that polypharmacy may worsen the adherence of elderly people with chronic diseases [29,30] and may contribute to adverse events such as falls [31].…”
Section: Discussionmentioning
confidence: 82%
“…Overall, our results indicated that advanced age, marital status, smoking status, and functional ability were correlated with medication adherence amongst older adults who were pre-frail, while advanced age was found to have a significantly link among frail older adults. Over the years, few studies have examined factors associated with medication adherence with an emphasis placed on older people with frailty and pre-frailty, while age, gender, and education level have been related to medication adherence in patients who have diabetes, hypertension, and tumor [ 14 , 15 , 29 ]. The present study demonstrated that factors including gender, residence, and depressive symptoms were related to medication adherence for both groups, while these variables were not significantly related.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, much emphasis has been placed on medication regimens among older people challenged by comorbidities such as diabetes, hypertension, and tumor [ 14 , 15 , 16 , 17 , 18 , 19 ]. Nonetheless, research that specifically determines barriers and facilitators to influence the development of medication adherence in frail or pre-frail older people, has been largely understudied.…”
Section: Introductionmentioning
confidence: 99%